The financial impact of a withdrawn ISO 9001 certificate - Cândido, Carlos (2016)
The authors thank two anonymous referees for their insightful comments and helpful suggestions. The authors thank also Jennifer Nicole Elston and Mário Luís Miranda Soares for their help. Finally, the authors are pleased to acknowledge the financial support from Fundação para a Ciência e a Tecnologia and FEDER/COMPETE (grant UID/ECO/04007/2013).